Quantitative formulation of excipients in "Angiolin" tableting - Bidnenko, O. S.; Бідненко, Олександр Сергійович (Буковинський державний медичний університет, 2017)
For the last three years the cardiovascular diseases make up 66% in general Ukrainian structure of mortality, while in most European countries, this figure does not exceed 50%. In quantitative formulation development of "Angiolin" tablets we used an active substance - angiolin substance and several excipients. Substance of angiolin (Public Factory "Chemical plant", Kharkiv) was derived by SPA "Farmatron" according to agreement of joint research. The excipients that were used for “Angiolin” tablets, are certified and produced in Ukraine and abroad. In studies we used the latest and modern equipment: tableting press, uniformity tester for tablet mass determination, tester for tablet friability, hardness, and disintegration time determination. The 5 quantitative factors were studied during studies. The amount of calcium stearate was 1 % while tablet formulating, in stage of granules lubrication. When according to the experiment plan the average “Angiolin” weight was less than 0.32 for the required dose number, we added MCC 101, which previously showed the best results.